Succession of family businesses in Singapore : 3 case studies. - Tan, Li Li. (2008)
This project investigated the following: the US benchmark of the succession process, the issue of corporate governance with relation to the succession process, an analysis of three Singapore-based family businesses and the way the three companies are handling the issue of succession.